Penerapan Model Problem Based Learning dalam Pembelajaran Tematik Terpadu di Kelas V Sekolah Dasar - Rahma Yelnosia; Taufina Taufik (Universitas Negeri Padang, 2020)
This research aims to describe the application of the Problem Based Learning model in integrated thematic learning in elementary schools. This research is motivated by several problems. In terms of planning, teachers are not developing the learning model to be used. In terms of implementation, students tend to listen to teacher explanations, student-centered learning is less visible, students are less active and do not develop critical thinking skills in learning. The Problem Based Learning Model is a learning model that involves students actively in learning, so that they can develop critical thinking skills and practice independent learning skills in a problem. The method used in this research uses literature study (library research) through literature review to assess the analysis of various sources used. The data learning technique in this research is the literature study technique, which is carried out by collecting relevant sources with the application of the Problem Based Learning model in integrated thematic learning in primary schools, both from books, articles, and reputable journals. Data analysis in this study uses content analysis method, which is carried out in certain stages to extract the essence of the idea or information which then draws conclusions. The results of this study indicate that the Problem Based Learning model is effectively applied in integrated thematic learning in elementary schools.